A strength and conditioning approach for ice hockey. - Nightingale, S. C. (Strength and Conditioning Journal, 2014)
Ice hockey is a mainstream sport in some countries but not worldwide. This creates limitations on the time and money available for ice hockey organizations. Such circumstance creates limitations on the time and money available for organizations to devote to extensive off-ice conditioning. This article educates coaches and players into the benefits of off-ice conditioning, even in an environment of scarce resources, and to provide an example of a comprehensive year-long conditioning program for ice hockey. Maximum strength and maximum power development strategies are discussed, along with a suggested strategy for the maintenance of gains across a physically demanding season.